Natural biomass-derived carbon dots as a potent solubilizer with high biocompatibility and enhanced antioxidant activity - Wu, Tong; Li, Menghan; Li, Tingjie; Zhao, Yafang; Yuan, Jinye; Zhao, Yusheng; Tian, Xingrong; Kong, Ruolan; Zhao, Yan; Kong, Hui; Zhang, Yue; Qu, Huihua (Frontiers in Molecular Biosciences, 2023)
Numerous natural compounds exhibit low bioavailability due to suboptimal water solubility. The solubilization methods of the modern pharmaceutical industry in contemporary pharmaceutical research are restricted by low efficiency, sophisticated technological requirements, and latent adverse effects. There is a pressing need to elucidate and implement a novel solubilizer to ameliorate these challenges. This study identified natural biomass-derived carbon dots as a promising candidate. We report on natural fluorescent carbon dots derived from Aurantia Fructus Immatures (AFI-CDs), which have exhibited a remarkable solubilization effect, augmenting naringin (NA) solubility by a factor of 216.72. Subsequent analyses suggest that the solubilization mechanism is potentially contingent upon the oration of a nanostructured complex (NA-AFI-CDs) between AFI-CDs and NA, mediated by intermolecular non-covalent bonds. Concomitantly, the synthesized NA-AFI-CDs demonstrated high biocompatibility, exceptional stability, and dispersion. In addition, NA-AFI-CDs manifested superior free radical scavenging capacity. This research contributes foundational insights into the solubilization mechanism of naringin-utilizing AFI-CDs and proffers a novel strategy that circumvents the challenges associated with the low aqueous solubility of water-insoluble drugs in the field of modern pharmaceutical science.